ILRI Medium-term plan 1999-2001. Improving the productivity of smallholder livestock systems and protecting the natural resources that support them - International Livestock Research Institute (International Livestock Research Institute, 1998)
This medium term plan highlights current status, including 1997 results and recent Developments with particular reference to current programme, 1997 achievements, new Developments, public concerns, financial Developments and staffing Developments. Highlights of changes for 1998/99, highlights of changes for 2001, changes in milestones, collaboration highlights, project cost components, centre staffing highlights, centre financial health indicators, and financing plan are other topics of discussion. The financial tables presented lists ILRI research agenda requirements by undertaking, and by CGIAR activity, allocation of project costs, research agenda with reference to investment, commodity, region, expenditure and staff composition. ILRI cash requirement, revenue flow and currency shares as well as ILRI statement of financial position is also presented. As an annex, the twenty ILRI projects are outlined. Under each project - objectives, outputs, milestones, expected gains, duration, cost and collaboration and product delivery are highlighted.